PS02.165: THE INCIDENCE OF CHYLOTHORAX AFTER ESOPHAGECTOMY CAN BE REDUCED BY LOW FAT TUBE FEEDING. (14th September 2018) - Schurink, Bernadette; Mazza, Elena; Ruurda, Jelle; Roeling, Tom; Steenhagen, Elles; Bleys, Ronald; Hillegersberg, Richard
Abstract: Background: Chylothorax is a treacherous complication after esophagectomy associated with significant morbidity. Early enteral nutrition after surgery is important for recovery, but increases the pressure in the lymphatic system due to the absorption of triglycerids. To lower the incidence of chylothorax after esophagectomy, the use of low fat-containing tube feeding was evaluated as a standard of care following esophagectomy. Methods: All consecutive patients who underwent an esophagectomy with gastric tube reconstruction and placement of jejunostomy at the UMC Utrecht between the 1 st of January 2012 and the 31 st of December 2017 were included. Tube feeding was started as standard of care on postoperative day 1 with a normal fat-containing formula in the period between 2012 and 2014 and with a low fat-containing formula between 2014 and 2017. The clinical diagnosis of chylothorax was confirmed by triglyceride levels > 1.24mmol/L in 27 patients (61.4%). Results: Between 2012–2017 200 patients were included; 88(44.0%) received normal fat-containing tube feeding, 112(56.0%) low fat-containing tube feeding. Chylothorax was significantly less observed in the low fat formula group (n = 15, 13.4% versus n = 29, 33%, P = 0.001) No difference was seen in drain output, triglyceride levels in the pleura fluid, treatment strategy and hospital mortality. At multivariable analysis normal fat formula was associated with a 5.1 [2.1–12.1] odds for postoperative chylothorax. Other factors independently associated with chylothorax were transthoracic resection, anastomotic leakage, number of resected lymph nodes, and lower body mass index. Conclusion: Administration of low fat-containing tube feed after esophagectomy lowers the incidence of chylothorax. Disclosure: All authors have declared no conflicts of interest.